2015
DOI: 10.15639/teflinjournal.v26i1/17-35
|View full text |Cite
|
Sign up to set email alerts
|

Types of Language Learning Strategies Used by Tertiary English Majors

Abstract: This study investigated the types of language learning strategies used by 73 English majors from the School of Humanities in Universiti Sains Malaysia. Using questionnaires adopted from Oxford's (1990) Strategy Inventory of Language Learning (SILL) and focus group interviews, the study also examined the English major students' perceptions of using language learning strategies while learning English. The results revealed that the English majors were generally high users of all six types of language learning str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…Interestingly, studies related to the use of the six main categories of LLS in the SILL, at different proficiency levels, have displayed consistent results with profiles of the strategy use. Several studies, for example, have noted that all three proficiency levels favored meta-cognitive strategies (Chuin, & Kaur, 2015;Hayati, 2015;Idham, 2014;Magogwe, 2005;Radwan, 2011). Similarly, Radwan (2011) who conducted studies in Oman found that both proficient and less proficient learners used meta-cognitive strategies at a high frequency.…”
mentioning
confidence: 99%
“…Interestingly, studies related to the use of the six main categories of LLS in the SILL, at different proficiency levels, have displayed consistent results with profiles of the strategy use. Several studies, for example, have noted that all three proficiency levels favored meta-cognitive strategies (Chuin, & Kaur, 2015;Hayati, 2015;Idham, 2014;Magogwe, 2005;Radwan, 2011). Similarly, Radwan (2011) who conducted studies in Oman found that both proficient and less proficient learners used meta-cognitive strategies at a high frequency.…”
mentioning
confidence: 99%
“…So teachers have to equip themselves with proper instrument of language learning, so they are able to determine their students' language learning strategy. Moreover, they have to make sure that students are able to use their strategies to mastering any new learning situation (Chuin & Kaur, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This current study adopts the framework developed by Oxford (1990), which is one of the most widely-accepted classification scheme involving a variety of language learning strategies. The SILL was chosen for this study because it is the most frequently used strategy scale and it is highly reliable and valid (Ellis, 1994;Sung, 2011;Judge, 2012;Barrios, 2015;Chuin & Kaur, 2015), both in its original English version and in translation as in the present case.…”
Section: Instruments: Strategy Inventory For Language Learning (Sill)mentioning
confidence: 99%
“…The instructor's goal is to develop a student that is able to evaluate and identify the appropriate strategy that could solve the language learning task. Furthermore, the instructor has to make sure that students are able to transfer the strategies that they have mastered to any new learning situation (Chuin & Kaur, 2015). In any case, just one methodology might not serve for all the degree courses; the specific characteristics of the students need to be borne in mind (Gil et al, 2009), as well at their perceptions of their use of strategy categories.…”
Section: Conclusion and Suggestionsmentioning
confidence: 99%